Non-Pharmacological Interventions for Minimizing Physical Restraints Use in Intensive Care Units: An Umbrella Review - Cui, Nianqi; Yan, Xiaoli; Zhang, Yuping; Chen, Dandan; Zhang, Hui; Zheng, Qiong; Jin, Jingfen (Frontiers in Medicine, 2022)
Background There is a relationship between the application of physical restraints and negative physiological and psychological effects on critically ill patients. Many organizations have supported and advocated minimizing the use of physical restraints. However, it is still common practice in many countries to apply physical restraints to patients in intensive care. Objective This study aimed to assess the effectiveness of various non-pharmacological interventions used to minimize physical restraints in intensive care units and provide a supplement to the evidence summary for physical restraints guideline adaptation. Methods Based on the methodology of umbrella review, electronic databases, including Cochrane Database of Systematic Reviews, Joanna Briggs Institute Database of Systematic Reviews and Implementation Reports, MEDLINE, EMBASE, CINAHL, Web of Science, PsycInfo/Psyc Articles/Psychology and Behavioral Science Collection, China National Knowledge Infrastructure, SinoMed, and Wanfang Data, were searched to identify systematic reviews published from January 2016 to December 2020. Two independent reviewers undertook screening, data extraction, and quality appraisal. The methodological quality of systematic reviews was evaluated by AMSTAR 2. Evidence quality of each intervention was assessed according to GRADE. The corrected covered area was calculated as a measure of overlap. Results A total of 47 systematic reviews were included in the umbrella review, of which six were evaluated as high quality, five were of moderate quality, and the rest were of low or critically low quality. The corrected covered area range was from 0.0 to 0.269, which indicated that there was mild overlap between systematic reviews. The included systematic reviews evaluated various types of non-pharmacological interventions for minimizing physical restraints in intensive care units, which included multicomponent interventions involving healthcare professionals' education, family engagement/support, specific consultations and communication, rehabilitation and mobilization (rehabilitation techniques, early mobilization, inspiratory muscle training), interventions related to reducing the duration of mechanical ventilation (weaning modes or protocols, ventilator bundle or cough augmentation techniques, early tracheostomy, high-flow nasal cannula), and management of specific symptoms (delirium, agitation, pain, and sleep disturbances). Conclusion The number of systematic reviews related to physical restraints was limited. Multicomponent interventions involving healthcare professionals' education may be the most direct non-pharmacological intervention for minimizing physical restraints use in intensive care units. However, the quality of evidence was very low, and conclusions should be taken with caution. Policymakers should consider incorporating non-pharmacological interventions related to family engagement/support, specific consultations and communication, rehabilitation and mobilization, interventions related to reducing the duration of mechanical ventilation, and management of specific symptoms as part of the physical restraints minimization bundle. All the evidence contained in the umbrella review provides a supplement to the evidence summary for physical restraints guideline adaptation. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=242586, identifier: CRD42021242586.